CONSTRUCTED WETLANDS FOR NITROGEN REMOVAL AND SIMULTANEOUS REUSE OF DOMESTIC SEWAGE - Silva, Selma Cristina; Bernardes, Ricardo Silveira; Ramos, Maria Lucrécia Gerosa (Revista Eletrônica de Gestão e Tecnologias Ambientais, 2024)
This study evaluated the behavior of vertical flow constructed wetland (VFCW), planted with irrigated rice (Oryza sativa L.), specie BRS-GO Guará, and a vertical flow soil filter without plant (VFSF-CTR), as control, both on a reduced experimental scale. The objective was the removal and recovery of N from domestic sewage, using soil latossoil red-yellow (LRY) mixed with medium sand (modified LRY) as support medium. The operation of VFCW and VFSF-CTR for ten months and two rice crop cycles, used three different hydraulic loading rates - HLR (4.0, 8.0 and 15.0 cm/d); with three repetitions, totalizing eighteen experimental units. For the VFCW, the total Kjeldahl nitrogen (KTN) and N-NH4+ removal efficiencies, ranged from 86% to 95%; and, for VFSF-CTR, from 79 to 94%; with the rice crop favoring higher efficiencies in KTN removal, independent of HLR. Both systems showed tertiary treatment removal efficiency in a single stage; in addition, the variations in the removal efficiencies were minimal when operated with HLR of 15 cm/d. There was great accumulation of KTN and mineral N (N-NH4+ and N-NO3-) in soil, mainly in the 0-5 cm soil layer, which can be used for fertilization of other crops. There was also N immobilised in microbial biomass (MBN). This rapid fertilisation improved the soil quality in a short term (ten months of sewage application) and provided the production of grains and vegetable biomass for human and animal food. The VFCW presented good results, either operated with low or high hydraulic loads, showing larger operational flexibility.